Economic theory and social science: alienation, fetishism, colonization - Romero Reyes, Antonio (2005)
The paper essay deals with broad issues in dealing with the historical and contemporary development of academic disciplines in the social sciences. lt draws a distinction between economics and the other "social sciences". The argument is based on the use of such categories as alienation and fetishism.lt involves a historical review to gauge the influence on economics of the mechanistic paradigm of the Newtonian revolution, as well as the transformation of political economy into economic theory. The paper deals with the concepts of alienation and fetishism in Marx, befare discussing theissues of 'eternización' and 'colonización'.